Phytochemicals, characterization and antimicrobial tests of red betel leaves on three solvent fractions as candidates for endometritis phytotherapy in Aceh cattle, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Armansyah T, Siregar TN, Suhartono, Sutriana A. 2022. Phytochemicals, characterization and antimicrobial tests of red betel leaves on three solvent fractions as candidates for endometritis phytotherapy in Aceh cattle, Indonesia. Biodiversitas 23: 2111-2117. The use of antibiotics to treat endometritis in cattle carries with it some weaknesses in the form of toxicity risks and unexpected side effects. The use of medicinal plants as antimicrobials and immunomodulators has the potential to be an alternative therapy. Red betel leaves could be considered viable candidates for phytotherapy in cattle with endometritis. This study aimed to determine the differences in biological activity and antibacterial ability of red betel leaf through the use of three different solvents, namely n-hexane, ethyl acetate, and ethanol. The highest yield of betel leaf extract was obtained from the ethyl acetate solvent fraction consisting of flavonoids, terpenoids, steroids, tannins, phenolics, and saponins. The highest biological compounds in red betel leaf identified by GC-MS in n-hexane solvent, ethyl acetate, and ethanol were 5-isobutylidene-N, N-dimethylbarbituric acid, benzenamine, 4,4' - (1,2-ethenediyl) bis-, and 9-octadecadienoic acid, respectively. Among the three solvent fractions of red betel leaf extract, it was observed that ethyl acetate exhibited higher antibacterial activity than hexane and ethanol. Hence, it can be concluded that ethyl acetate extract of red betel leaves solvent has secondary metabolites and better antibacterial potential than ethanol and n-hexane solvents.
Keywords: Ethanol, ethyl acetate, n-hexane, red betel